2017
DOI: 10.18632/oncotarget.18221
|View full text |Cite
|
Sign up to set email alerts
|

In vivo autophagy and biogenesis of autophagosomes within male haploid cells during spermiogenesis

Abstract: Autophagy is a unique catabolic pathway that is linked to several physiological processes. However, its role in the process of spermiogenesis is largely unknown. The aim of the current study was to determine the in vivo role of autophagy and the origin of autophagosome membrane biogenesis within male haploid cells. Our immunohistochemistry results demonstrated that LC3 and ATG7 localization were increased dramatically in round to elongated spermatids (haploid cells) towards the lumen of seminiferous tubules, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…Comparable autophagosome structures were not observed in Sertoli cells from both wild-type ( Fig 1A, panel e ) or Stra8 -deficient testes ( Fig 1B, panel c and e ). This is consistent with a recent report that autophagy was not detected in spermatogonia, early spermatocytes and Sertoli cells in rat testes [19]. The autophagosome structures observed in Stra8 -deficient germ cells were located in the cytoplasmic region of both non-degenerative (cells with intact membrane) ( Fig 1B, panels f-i ) and degenerative cells ( Fig 1B, panel j ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Comparable autophagosome structures were not observed in Sertoli cells from both wild-type ( Fig 1A, panel e ) or Stra8 -deficient testes ( Fig 1B, panel c and e ). This is consistent with a recent report that autophagy was not detected in spermatogonia, early spermatocytes and Sertoli cells in rat testes [19]. The autophagosome structures observed in Stra8 -deficient germ cells were located in the cytoplasmic region of both non-degenerative (cells with intact membrane) ( Fig 1B, panels f-i ) and degenerative cells ( Fig 1B, panel j ).…”
Section: Resultssupporting
confidence: 93%
“…Our observation that autophagy is being actively suppressed by STRA8 during meiotic initiation in mouse spermatogenesis is in accordance with a recent study of autophagy in rat spermatogenesis, in which autophagy was found only to be activated during late meiotic spermatocytes but not in spermatogonia and early spermatocytes [19]. This is in line with the finding in yeast, in which autophagy is required for proper meiotic chromosome segregation [51].…”
Section: Discussionsupporting
confidence: 92%
“…Removal of Atg7 did not affect development of earlier germ cell types indicating that autophagy is less active in these cells (Shang et al, 2016). This notion was corroborated by a more recent report that found the highest abundance of autophagosomes in spermatids (Yang et al, 2017). Taken together, these data indicate that autophagy contributes to acrosome maintenance, spermatid polarization and degradation of cytoplasmic components during spermiogenesis.…”
Section: Autophagy and Mitophagy During Spermatogenesissupporting
confidence: 72%
“…The known biology of autophagy was revolutionized following the identification of autophagy genes within mammals [26]. ATG7 is the most essential member of an autophagy-related gene family that encodes the E1-like enzyme, which facilitates both LC3 and other autophagy-related genes [27].…”
Section: Introductionmentioning
confidence: 99%